WEB-BASED SCORING APPLICATION FOR MONITORING AND EVALUATION OF HIGHER EDUCATION ACCREDITATION RANKING - Hasanuddin Hasanuddin; Andie Andie (UPT Publication and Journal Management, Islamic University of Kalimantan, 2024)
This study presents the development of a web-based application designed to assist in monitoring compliance with the PEPA (Instrument of Higher Education Accreditation) scoring system. Utilizing CSS Bootstrap 5.3 for the interface, MySQL 8.2.4 for database management, and PHP 8.2.4 with native coding, the application features two user levels: Admin for system management and Study Program for data input. The primary objective of the application is to recapitulate PEPA scoring and provide alerts to Study Programs when their scores fall below the required standards. In accordance with the Ministry of Education and Culture Regulation No. 5 of 2020, which mandates BAN-PT's responsibility to monitor accreditation compliance, this application facilitates continuous monitoring of submitted data. By doing so, it helps prevent non-compliance, ensuring that Study Programs and Higher Education Institutions maintain their accreditation status and avoid the need for re-application.